Precisely controlled synthesis of Co/N species containing porous carbon for oxygen reduction reaction via anion exchange and CO2 activation. (5th January 2022) - Shu, Yasuhiro; Fujimoto, Yugo; Miyake, Koji; Uchida, Yoshiaki; Tanaka, Shunsuke; Nishiyama, Norikazu
Abstract : The synthesis strategy of highly dispersed Co/N-doped porous carbon materials using anion exchange resin and ionic liquids. Abstract : For wide use and cost reduction of proton exchange membrane fuel cells (PEMFCs), the development of transition-metal-doped porous carbon (TMPC) electrocatalysts for the oxygen reduction reaction (ORR) is urgently needed. Herein, we report a new strategy for designing CoN x -doped carbon materials with fine-tuned porosity via anion exchange and CO2 activation processes. Highly dispersed CoN x species are introduced into carbon materials by the anion exchange process. After that, the porosity of the CoN x -doped carbon is controlled by an optimized CO2 activation. The precisely controlled active sites and porosity of the obtained catalyst (Co/N/C-act) lead to an extraordinary ORR performance in an alkaline medium. This work paves a new direction in development strategy not only for electrocatalysts but also for other potential applications, such as water splitting and supercapacitors.